2021
DOI: 10.3390/ijerph18010332
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarette-Only and Dual Use among Adolescents in Ireland: Emerging Behaviours with Different Risk Profiles

Abstract: E-cigarette-only use and dual-use are emerging behaviours among adolescent nicotine product users which have not yet been sufficiently explored. This study examines the prevalence of, and the factors associated with, nicotine product use in adolescence. The study is a cross-sectional analysis of the 2018 Planet Youth survey completed by 15–16 year olds in the West of Ireland in 2018. The outcome of interest was current nicotine product use, defined as use at least once in the past 30 days. A main effects multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
2
19
0
1
Order By: Relevance
“…This leads us to speculate, for example, that boys may be targeted through gaming platforms and that girls’ rapidly increasing e-cigarette use may be related to their greater social media use. The scope within these parallel gendered domains for targeted marketing of e-cigarettes by industry merits further research and we also support calls for regulatory action to prohibit sponsored e-cigarette content on social media platforms used by youth [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This leads us to speculate, for example, that boys may be targeted through gaming platforms and that girls’ rapidly increasing e-cigarette use may be related to their greater social media use. The scope within these parallel gendered domains for targeted marketing of e-cigarettes by industry merits further research and we also support calls for regulatory action to prohibit sponsored e-cigarette content on social media platforms used by youth [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 56%
“…Gender being an incomplete explanation of the observed differences in teenage e-cigarette use, we draw attention to intersectionality [ 44 ] as a promising framework to achieve new understandings of teenage tobacco use. Although intersectionality has been examined in relation to adult smoking cessation (e.g., [ 45 , 46 ]), there is little or no research to date on teenage tobacco use (and consequent health inequalities) that captures the complexity of “multiple aspects of identity” [ 41 ], employing analyses at the intersections of, for example, categories of gender, race, class/SES, disability, sexuality, and religion. More complex conceptual analyses are needed to generate new insights into this emergent and increasing problem of new tobacco product use by young people.…”
Section: Discussionmentioning
confidence: 99%
“…We know that heavier exposure to advertisements and e-cigarette content in social media posts is associated with a greater risk for e-cigarette use among adolescents, and even brief exposure to e-cigarette content on social media has been found to be associated with greater intention to use and more positive attitudes toward e-cigarettes (38). The scope within these parallel gendered domains for targeted marketing of e-cigarettes by industry merits further research and we also support calls for regulatory action to prohibit sponsored e-cigarette content on social media platforms used by youth (38,39).…”
Section: Gender Differences In E-cigarette Usesupporting
confidence: 59%
“…These findings are of concern as other cross-sectional studies have reported that children and adolescents who use ENDS and/or ENNDS have different psychological profiles to current smokers, and would have otherwise have been at low risk of smoking. [ 58 61 ] As such, there is an urgent need for governments internationally to take action to regulate the availability and marketing of ENDS/ENNDS products to children and adolescents.…”
Section: Discussionmentioning
confidence: 99%